Coagulant Capacity of Moringa (Moringa Oleifera) Seed on NaCl Solution - Sibulo, Vanesa; Abram, Paulus H. (Jurnal Akademika Kimia, 2023)
Moringa seeds are one of the natural coagulant ingredients that contain protein and carbohydrates that can be used in water purification, especially in reducing turbidity. This study aims to determine the level of NaCl coagulated by Moringa seed powder. The capacity or coagulation ability of Moringa seed powder is measured by the percentage of NaCl in the solution coagulated by Moringa seed powder. To achieve this purpose, several experiments have been used, namely variations in the concentration of NaCl as samples including; 0.5 %, 1 %, 3%, and 5% with treatment using Moringa seed powder as much as 1 g, 3 g and 5 g—determination of NaCl content using Flame Photometers BWB Technologies. The results of this study indicate that the optimum level of NaCl coagulated by Moringa seed powder is 3 %. The concentration can increase the effectiveness of reducing NaCl levels by obtaining a coagulated percentage value of 95.30 %.